Chemical Speciation of Copper in a Salt Marsh Estuary and Bioavailability to Thaumarchaeota - Whitby, Hannah; Hollibaugh, James T.; van den Berg, Constant M. G. (Frontiers in Marine Science, 2017)
The concentrations of dissolved copper (Cud), copper-binding ligands, thiourea-type thiols and humic substances (HSCu) were measured in estuarine waters adjacent to Sapelo Island, Georgia, USA, on a monthly basis from April to December 2014. Here we present the seasonal cycle of copper speciation within the estuary and compare it to the development of an annually occurring bloom of Ammonia Oxidising Archaea (AOA), which require copper for many enzymes. Two types of complexing ligands (L1 and L2) were found to dominate with mean complex stabilities (log K′CuL) of 14.5 and 12.8. Strong complexation resulted in lowering the concentration of free cupric ion (Cu2+) to femtomolar (fM) levels throughout the study and to sub-fM levels during the summer months. A Thaumarchaeota bloom during this period suggests that this organism manages to grow at very low Cu2+ concentrations. Correlation of the concentration of the L1 ligand class with a thiourea-type thiol and the L2 ligand class with HSCu provide an interesting dimension to the identity of the ligand classes. Due to the stronger complex stability, 82 - 99% of the copper was bound to L1. Thiourea-type thiols typically form Cu(I) species, which would suggest that up to ~90% copper could be present as Cu(I) in this region. In view of the very low concentration of free copper (pCu >15 at the onset and during the bloom) and a reputedly high requirement for copper, it is likely that the Thaumarchaeota are able to access thiol-bound copper directly.